Well-defined non-symmetric NHC-iron(III) catalyst for photoinduced atom-transfer radical polymerization of methyl methacrylate - Figueiredo, Maria L.B. [UNESP]; Bignardi, Camila [UNESP]; Pesqueira, Naralyne M. [UNESP]; Machado, Antonio E.H.; Carvalho-Jr, Valdemiro P. [UNESP]; Nascimento, Otaciro R.; Goi, Beatriz E. [UNESP] (Elsevier, 2024)
Photoinduced atom transfer radical polymerization (photo-ATRP) has emerged as a prominent technique in contemporary polymer chemistry, offering a potent means to create precisely structured materials. Well-defined catalysts are essential for controlling the growth of polymers with reproducible results; however, most photo-ATRP catalytic systems involve mixing the metal salt with the ligand. Herein we present a well-defined iron(III) based photo-ATRP catalyst bearing bidentate NHC ligand, 3-Methyl-1-phenyl-1H-3,1-benzimidazol-3-ium iodide (Pmb). The [FeBr(Pmb)2] was successfully synthesized and fully characterized by FTIR, UV–Vis, and EPR spectroscopic studies, elemental analysis, MALDI-TOF mass spectrometry, and computational studies. [FeBr(Pmb)2] was employed as the catalyst for photo-ATRP of methyl methacrylate (MMA) under ultraviolet light irradiation (365 nm). The catalytic activity of [FeBr(Pmb)2] in the photo-ATRP of MMA was evaluated under different conditions using EBPA as the initiator. The polymerizations showed robust activity, yelding in polymers with controlled molecular weights and a narrow molecular weight distribution (MWD). Remarkably, this was achieved with low catalysts loading (102.6 ppm), mainly at the molar ratio [MMA]/[EBPA]/[Fe] = 200/1/0.04. Well-defined polyMMA was synthesized and temporal control over photo-ATRP was successfully demonstrated through “on/off” experiments. For example, photo-ATRP of MMA with a molar ratio of [200/1/0.04] after 12 h at T = 25 °C in bulk resulted in PMMA with a polydispersity (Ð) of 1.15 at 50 % monomer conversion.
Keywords: Methyl methacrylate; N-heterocyclic carbine; Temporal control